Multi-wavelength oscillating and transverse mode switching in an all few-mode fiber laser based on polarization manipulation. (September 2019) - Li, Hongxun; Yan, Ke; Dong, Zhipeng; Tao, Runxia; Gu, Chun; Yao, Peijun; Xu, Lixin; Zhang, Rui; Su, Jingqin; Zhan, Qiwen
Highlights: The polarization dependence of the fiber Bragg grating is proved. Multi-wavelength operation and switchable transverse mode are realized. Azimuthally and radially polarized beams can be easily generated. Abstract: We have proved the polarization dependence of the fiber Bragg grating (FBG), and demonstrated an all few-mode fiber laser that can realize multi-wavelength oscillation and switchable transverse modes simultaneously based on the polarization dependence of FBG. In this fiber laser, single-, dual- and triple-wavelength oscillation can be realized by merely adjusting the polarization controller inside the cavity. Three output transverse modes including fundamental mode, second-order mode, and hybrid modes can be switched as the laser operates at three different single-wavelengths correspondingly. In addition, azimuthally and radially polarized beams can be easily generated. This all few-mode fiber laser scheme may play a more significant role in wavelength division multiplexed (WDM) systems, mode division multiplexed (MDM) systems, sensing, and so on.